THE ROLE OF ARCHITECTURAL HERITAGE IN TOURISM AND ECONOMIC DEVELOPMENT: CASE STUDY OF TEBESSA, ALGERIA - Grib Aissa; Brahmi Sami (International Journal of Innovative Technologies in Social Science, 2024)
The research explores the importance of architectural and urban heritage for its positive impacts on cities and societies. It highlights how such heritage embodies cultural identity, connects past and present, and promotes tourism and economic development. Tebessa, in eastern Algeria, serves as a case study due to its rich architectural and urban heritage, influenced by Phoenician, Numidian, Greek, Roman, Byzantine, and Islamic civilizations.Key landmarks in Tebessa include the Temple of Minerve, Caracalla Gate, Byzantine Wall, Roman Theatre, Roman Church, Archaeological Park, and Ancient Mosque. These sites create an open archaeological space within the urban fabric, serving as cultural heritage and vital resources for tourism and economic revitalization. The research initially adopts a theoretical approach to identify and describe various heritage sites. It then employs fieldwork, involving the Directorate of Tourism, the Directorate of Culture, and the Department of Archaeological Sites, to assess the status and significance of these monuments.Findings reveal several issues, such as the lack of strategic and institutional efforts to protect and utilize the heritage for cultural tourism and economic development. There is significant neglect and deterioration due to inadequate restoration programs and weak promotional initiatives. The research recommends adopting a comprehensive, multi-dimensional strategy for preserving the heritage of Tebessa, including comprehensive projects, legal frameworks, digital integration, and a participatory management approach. Collaboration with local and international heritage organizations and educational programs to raise awareness are also essential. These measures aim to preserve the architectural heritage and boost tourism in Tebessa.